Esomeprazole’s Role in Enhancing Colonic Anastomotic Healing Post-Ischemic Injury in the Rat Model - Faruk Pehlivanli; Oktay Aydin; Mehmet Selçuk Mısırlıgil; Kevser Peker; İlker Kaplan (Medicina)
Background and Objectives: Colonic anastomotic leaks are still a critical cause of morbidity and mortality. The study aimed to investigate the effects of esomeprazole on anastomotic healing after left colon anastomosis in rats with an ischemic colon. Material and Methods: Thirty-five male Wistar albino rats were divided into acute (CONTROL-A, ESP-A) and chronic (CONTROL-C, ESP-C) stage groups. Rats in the CONTROL-A and CONTROL-C groups underwent colonic anastomosis after hypoxia-reperfusion injury in the colon, and intraperitoneal saline was administered for three and ten days, respectively. Intraperitoneal 10 mg/day esomeprazole was given to the rats in the ESP-A and ESP-C groups for three and ten days after similar surgical procedures. Then, at scheduled times, 2 cm proximal and distal regions of the anastomosis line were resected, and bursting pressure was measured. Hydroxyproline (HYP), myeloperoxidase (MPO), malondialdehyde (MDA), caspase-3 (CSP3) and catalase (CAT), nitric oxide (NO), reduced glutathione (RGT), superoxide dismutase (SOD), TNF-α, IL-6, aspartate aminotransferase (AST), alanine aminotransferase (ALT) levels were measured in tissue and blood serum samples. Results: In the acute stage, CAT, NO, RGT, and SOD values in ESP-A group were lower than CONTROL-A group values. In addition, TNF, IL-6, ALT, and AST values in the ESP-A group were higher than the CONTROL-A group values between groups (p < 0.05). However, HYP and burst pressure values were not different between the groups. In the chronic stage, CAT, NO, RGT, SOD, CSP3, and burst pressure values in the ESP-A group were higher than CONTROL-A group values (p = 0.05). In contrast, TNF, IL-6, ALT, AST, HYP, MPO, and MDA values in the ESP-A group were lower than the CONTROL-A group values (p < 0.05). Conclusions: These results suggest that esomeprazole has anti-inflammatory and antioxidant activity in the chronic phase of ischemia–reperfusion injury, thus protecting the intestinal tissue from ischemic damage and enhancing the healing of the anastomosis line.